Pengaruh Komitmen Kerja, Loyalitas Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Kementrian Agama Pesisir Selatan - Koko Nurhadi Yanto; Novi Yanti; Meri Dwi Anggraini (Fakultas Ekonomi, Universitas Ekasaktii, 2026)
This research aims to find out which is dominant in work commitment, work loyalty, work discipline and employee performance at the Pesisir Selatan Ministry of Religion Office and the influence of work commitment, work loyalty and work discipline on employee performance at the Pesisir Selatan Ministry of Religion Office partially and simultaneously. This research uses a quantitative approach. The research sample was 53 respondents. Data collection uses a valid and reliable questionnaire. Data analysis was carried out using multiple linear regression analysis, testing the t and F hypotheses. The results of the research. The dominant indicator in the work commitment variable is Discipline in work with a TCR value of 83.00%, work loyalty is Sense of belonging with a TCR value of 87.80% , work discipline is Justice and contributes to the realization of employee discipline with a TCR value of 84.80% and employee performance is Work Quantity with a TCR value of 87.60%, work commitment has a positive and significant effect on employee performance, work loyalty has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance and work commitment, work loyalty and work discipline has a positive and significant effect on employee performance at the Pesisir Selatan Ministry of Religion Office